Effectiveness of reading aloud strategies for developing reading habits - Sajid, Muhammad Khalid Mehmood; Hafizoah, Kassim; Hasan, Ghasan Adnan (Open Access Publishing Group, 2019)
Read aloud strategy is essential; it determines the success of the future. The focus of present study was on read-aloud strategy and other reading strategies. Mainly the purpose of this study was to check the effectiveness of different reading strategies, which could be helpful at elementary level. The present study was based on reading habits of students at elementary level. The study was conducted in a Govt. Girls Elementary School Fateh Wala, Multan. Data was collected from grade 8 students. Data was collected with the help of questionnaire; pretest, posttest was also used to collect data from students. A sample size of 25 students was taken in which ten were female, and 15 male students had participated. Ten teachers also participated in this research work in which 5 were male teachers and five were female. A comparative analysis was conducted for students reading habits with reading-aloud and silent reading strategy. Atlas ti 8 updated version was used for literature review. Results include the finding that read aloud strategy is better than silent reading and other reading strategies at elementary level.